Method for choosing appropriate investment periods to make arbitrage profit and explain stock returns - Peymany, Moslem (Serbian Journal of Management, 2022)
The current paper presents theoretical and experimental evidence to justify the need for paying attention to the investment horizon. Therefore, a criterion called the ‘Safest Investment Horizon’ (SIH) is utilized to select the appropriate investment horizon. To compute this quantity, a ratio called the ‘Safest Investment Ratio’ (SIR) is calculated, and the relationship between these criteria and arbitrage opportunities, along with methods for making an arbitrage profit through selecting an appropriate time horizon are discussed. Afterward, by applying this method for real-life data, the presence of arbitrage opportunities at different time horizons is confirmed. Furthermore, the effects of the time horizon on optimal portfolio composition are described. Finally, it is shown that these criteria outperform some of the conventional variables in CAPM, the 3-factor, and the 5-factor models for explaining stock returns and using SIH or SIR as a new variable increases the explanatory power of these models.